A Case Study on Culture Brokers and Their Role in Tourism Management in the Indigenous Community of Taquile Island in Puno, Peru. (4th February 2014) - Cherro Osorio, Sandra Guisela; Best, Gary
Abstract This study examines the role of culture brokers in the management of tourism in the indigenous community of Taquile Island. Culture brokers are individuals that have the ability to understand visitors' culture as well as their own. In‐depth interviews were conducted with culture brokers, members of the community and tourists to explore the topic from multiple perspectives. The findings suggest that their strong sense of identity has determined that culture brokers direct the course of action from inside and outside their society, while members of the community contribute from their positions, and this collaborative effort positively influences the tourist experience. Copyright © 2014 John Wiley & Sons, Ltd.